Reducing reflectivity of stimulated Raman scattering by discretely changing phase of incident light in inertial fusion plasmas. (13th December 2021) - Yang, T; Zhang, S T; Zhou, Y Z; Liu, D J; Li, X M; Liu, Z J; Cao, L H; Zheng, C Y; He, X T
Abstract: A new method to reduce the stimulated Raman scattering (SRS) in inertial confinement fusion conditions is proposed by changing the incident light phase discretely. The proposal is first examined by three-wave coupling equations and then verified by Vlasov simulations. A remarkable decreasing in SRS reflectivity is observed when the period of phase changing is less than 2 π / γ, where γ is the growth rate of SRS. By contrast, some simulations with continuously changing phase of incident light are carried out to compare their influence on SRS. In addition, the proposal may suppress the stimulated Brillouin scattering.